Delirium from the gliocentric perspective - Sfera, Adonis; Osorio, Carolina; Price, Amy I.; Gradini, Roberto; Cummings, Michael (Frontiers in Cellular Neuroscience, 2015)
Delirium is an acute state marked by disturbances in cognition, attention, memory, perception, and sleep-wake cycle which is common in elderly. Others have shown an association between delirium and increased mortality, length of hospitalization, cost, and discharge to extended stay facilities (1). Until recently it was not known that after an episode of delirium in elderly, there is a 63% probability of developing dementia at 48 months compared to 8% in patients without delirium (2)(3). Currently there are no preventive therapies for delirium, thus elucidation of cellular and molecular underpinnings of this condition may lead to the development of early interventions and thus prevent permanent cognitive damage. In this article we make the case for the role of glia in the pathophysiology of delirium and describe an astrocyte-dependent central and peripheral cholinergic anti-inflammatory shield which may be disabled by astrocytic pathology, leading to neuroinflammation and delirium. We also touch on the role of glia in information processing and neuroimaging.